Variable expression of Van der Woude syndrome in the same family - Ravi Kumar Mahajan; Sheikh Sarfraz Ali; Sana Jameel; Samik Sharma (Wolters Kluwer Medknow Publications, 2022)
Van der Woude syndrome is a rare congenital condition with autosomal dominant traits. This autosomal dominant syndrome had been reported to have a penetrance of 80% with variable expression.[1] This genetic disorder is characterized by the combination of lip pits, cleft lip with or without cleft palate, and cleft palate only. Even within the families, there is a wide variability of affected gene expressions. It is very important to establish the correct diagnosis so that genetic counseling can be recommended in such cases. Here, we report cases of Van der Woude syndrome in the same family having the same genetic inheritance with variable expression.